Economic Thought in the Soviet Union - Zauberman, Alfred (Review of Economic Studies, 1949)
Journal Article Economic Thought in the Soviet Union: II.—Economic Planning and Control Get access A. Zauberman A. Zauberman Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 2, 1949, Pages 102–116, https://doi.org/10.2307/2295720 Published: 01 January 1949